Financial Performance Analysis Using EVA and FVA Methods at PT. Gowa Makassar Tourism Development TBK Period 2017-2022 - Mutya Khaerunnisa; Asri Jaya; Nurlina, Nurlina (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the financial performance of PT. Gowa Makassar Tourism Development Tbk. The 2017-2022 period is measured using the Economic Value Added (EVA) and Financial Value Added (FVA) methods. The population in the research is all financial report data of PT. Gowa Makassar Tourism Development Tbk. while the sample in this research is the financial position report and profit and loss report for the 2017-2022 period. The data collection technique used is documentation technique. The data collected was analyzed using Economic Value Added (EVA) and Financial Value Added (FVA) calculations. The results in this study indicate that the financial performance of PT. Gowa Makassar Tourism Development Tbk. The 2017-2022 period measured using the Economic Value Added (EVA) method obtained positive results, meaning that PT. Gowa Makassar Tourism Development is able to create added economic value. Financial performance of PT. Gowa Makassar Tourism Development Tbk. The 2017-2022 period was measured using the Financial Value Added (FVA) method to obtain positive results. This means PT. Gowa Makassar Tourism Development is able to create added financial value, and it is said that PT. Gowa Makassar Tourism Development has good performance .